Association of polymorphisms in human platelet antigens with idiopathic thrombocytopenic purpura in Macedonians - Pavkovic M; Stojanovic A; Karanfilski O; Cevreska L; Spiroski M (Македонска академија на науките и уметностите, Одделение за биолошки и медицински науки = Macedonian Academy of Sciences and Arts, Section of Biological and Medical Sciences, 2012)
Idiopathic thrombocytopenic purpura (ITP) is an autoimmune disease characterized by thrombocytopenia due to the presence of platelet autoantibodies specific for platelet membrane glycoproteins, such as GPIIb/IIIa, GPIb/IX and GPIa/IIa. These autoantibodies cause an accelerated clearance of opsonized platelets by phagocytes and inhibition of platelet production. Human platelet antigen (HPA) systems HPA-1, HPA-2, HPA-3 and HPA-5 are components of platelet GP complexes GPIIb/IIIa, GPIb/IX and GPIa/IIa. The HPA system consists of more than 12 bi-allelic antigen polymorphisms in which a base-pair substitution leads to change in an amino acid sequence of a membrane glycoprotein expressed on the platelet surface. The aim of this study was to examine the association of HPA-1, HPA-2, HPA-3 and HPA-5 polymorphisms with idiopathic thrombocytopenic purpura. We performed genotyping of HPA-1, HPA-2, HPA-3, and HPA-5 systems in 60 patients with ITP and 120 healthy participants. Genotyping of HPA-1, -2, -3, and -5 alleles were performed by PCR and RFLP methods by using specific primers and restriction enzymes. Allele and genotype frequencies of HPA-1, HPA-3, and HPA-5 were not significantly different between patients and healthy participants. After Bonferroni adjustment a significant association in ITP patients with HPA-2 alleles (P=0.015, OR=1.923, CI=1.126-3.284) was found. Allele frequencies for HPA-2a were 0.852 in healthy participants and 0.750 in patients, and for HPA-2b 0.148 and 0.250 respectively. These results suggests that HPA-2b allele was more frequent in patients with ITP and may be involved in the formation of a specific autoepitope.